CCL-2 as a possible early marker for remission after traumatic spinal cord injury - Heller, Raban; Swing, Tyler; Kunzmann, Kevin; Daniel, Volker; Haubruck, Patrick; Akbar, Michael; Schmidmaier, Gerhard (Spinal cord. Series and cases, 2017)
Study design: Prospective observational study.Objectives:To describe the correlation between CCL-2, CCL-3, CCL-4 and CXCL-5 serum levels and remission after traumatic spinal cord injury (SCI) in a human protocol compared with animal studies. Setting: Germany, Rhineland-Palatinate (Rheinland-Pfalz).Methods:We examined the serum levels of CCL-2, CCL-3, CCL-4 and CXCL-5 over a 12-week period; in particular, at admission and 4, 9 and 12 h, 1 and 3 days and 1, 2, 4, 8 and 12 weeks after trauma. According to our study design, we matched 10 patients with TSCI and neurological remission with 10 patients with an initial ASIA A grade and no neurological remission. In all, 10 patients with vertebral fracture without neurological deficits served as control. Our analysis was performed using a Luminex Cytokine Panel. Multivariate logistic regression models were used to examine the predictive value with respect to neurological remission vs no neurological remission. Results: The results of our study showed differences in the serum expression patterns of CCL-2 in association with the neurological remission (CCL-2 at admission P=0.013). Serum levels of CCL-2 and CCL-4 were significantly different in patients with and without neurological remission. The favored predictive model resulted in an area under the curve (AUC) of 93.1% in the receiver operating characteristic (ROC) analysis. Conclusions: Our results indicate that peripheral serum analysis is a suitable concept for predicting the patient’s potential for neurological remission after TSCI. Furthermore, the initial CCL-2 concentration provides an additional predictive value compared with the NLI (neurological level of injury). Therefore, the present study introduces a promising approach for future monitoring concepts and tracking techniques for current therapies. The results indicate that future investigations with an enlarged sample size are needed in order to develop monitoring, prognostic and scoring systems.
Gesehen am 25.04.2018